МОНГОЛ ДАХЬ ПАРЛАМЕНТАТ ЁСНЫ ХӨГЖИЛ, БОЛОВСРОНГУЙ БОЛГОХ АРГА ЗАМ - Б.Эрдэнэдалай, (Politology, 2023)
In this article has taken development of Mongolian parliamentarism, perfection for requirement and avenue. It explains rules of seperation of power that Mongolian parliament and government's intercommunication. Parliamentary activities need more disclosure and more check of voters, mass media and others. It will reduce some positive effectives of Mongolian people's political attitude and parliamentarism.